2020
DOI: 10.3390/w12020362
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Substrate Available Water and Coir Amendment Rate in Pine Bark Substrates

Abstract: Water resources can be used more efficiently by including sustainable substrate components like coir that increase water-holding capacity. The first objective of this study was to evaluate the impact of coir amendment rate on plant available water and plant gas exchange, with the goal of optimizing substrate available water and determining the optimum coir amendment rate in a greenhouse environment. The second objective was to establish the optimum method of determining plant available water using either plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The bark-peat and bark fines had the greatest EAW and WBC values. Recent studies have shown increased proportions of water held within this −10 hPa to −100 hPa substrate water potential range to be available to plants from increased proportions of fiber and reductions in particle size for bark materials [12,36] x Water buffering capacity is water held between −50 and −100 hPa. w Available water is this research is calculated as the difference in measured container capacity and modeled volumetric water content at −1.5 MPa.…”
Section: Substratementioning
confidence: 99%
See 1 more Smart Citation
“…The bark-peat and bark fines had the greatest EAW and WBC values. Recent studies have shown increased proportions of water held within this −10 hPa to −100 hPa substrate water potential range to be available to plants from increased proportions of fiber and reductions in particle size for bark materials [12,36] x Water buffering capacity is water held between −50 and −100 hPa. w Available water is this research is calculated as the difference in measured container capacity and modeled volumetric water content at −1.5 MPa.…”
Section: Substratementioning
confidence: 99%
“…The bark-peat and bark fines had the greatest EAW and WBC values. Recent studies have shown increased proportions of water held within this −10 hPa to −100 hPa substrate water potential range to be available to plants from increased proportions of fiber and reductions in particle size for bark materials [12,36].…”
Section: Substratementioning
confidence: 99%
“…Eq. ( 6) may be easily graphically represented in a log-normal scale, where log scale (ordenates) de nes The general water balance equation for the root zone during a speci c area and time period is given by: I + P + CR = ETa + Dr + R + ΔS (7) where I is the net irrigation, P is the natural precipitation, CR is the capillary rise from the groundwater table to the root zone, ETa is the actual crop evapotranspiration, Dr is the drainage below the root zone, R is the runoff, and ΔS is the change in water storage within the root zone; the units for all these parameters are m 3 . Being capillary rise CR and runoff R zero during this speci c time area and period and being ΔS, P and Dr negligible due to high irrigation frequency; and being very low or no natural precipitation P, Eq.…”
Section: Theorymentioning
confidence: 99%
“…However, pine bark substrate has a higher air-filled porosity resulting in a lower water holding capacity than perlite [5]. In a pour through experiment, pine bark substrate had less available water and retained less nitrogen, i.e., NO 3 − -N and NH 4 + -N, implying more N would be drained out [6,7] when used. Although perlite is also porous, due to its smaller particle size it has a higher amount of plant available water [8].…”
Section: Introductionmentioning
confidence: 99%